Teacher transfers and the disruption of teacher staffing in the city of Sao Paulo - Gregory Elacqua; Leonardo Rosa (Inter-American Development Bank (IDB), 2023)
This paper analyzes preferences for certain school attributes among in-service teachers. We explore a centralized matching process in the city of Sao Paulo that teachers must use when transferring schools. Because teachers have to list and rank their preferences for schools, we can estimate the desirability of school attributes using a rank-ordered logit model. We show that the school's distance from the teacher's home, its average test scores, and teacher composition play a central role in teacher preferences. Furthermore, we document that preferences vary according to teacher characteristics such as gender, race, age, and academic subject.
Keywords: I21; I24; I25; I28; 330; teachers; teacher assignment; teacher transfers; centralized assignment; Brazil